#1forEquality: The Story of an Unlikely Victorious Campaign in the Making. (31st December 2019) - Casla, Koldo
Abstract: The UK government proudly affirms that the country has some of the strongest equalities legislation in the world, including the Equality Act 2010. For it to be true, however, the government should implement the legislation in its entirety, including the socio-economic duty (section 1 of the Act). That duty would require public authorities to actively consider how their decisions and policies of the highest strategic importance can increase or decrease inequalities of outcome. Regrettably, successive governments have failed to commence the duty, and therefore it is not technically binding on public authorities. It is encouraging that the duty was brought to life in Scotland in 2018 and the Welsh Government has announced they will follow suit in 2020. The socio-economic duty is potentially a useful lever to understand and address the structural causes of material inequalities and their negative effects on human rights and well-being. This article presents and draws conclusions from the strategic choices made by the people running #1forEquality, the national campaign to bring the socio-economic duty to life. The article introduces four key factors that contributed to making progress between 2017 and 2019, despite the limited resources available: a) the added value of merging advocacy and epistemic communities working on equality and on human rights; b) the engagement with political actors at key stages of the process; c) the combination of 'naming and shaming' and best practice; and d) the celebration of smaller victories along the way.